Smartphone Screen Testing, a Novel Pre-Diagnostic Method to Identify Sars-Cov-2 Infectious Individuals - Sandino-Garcia, A; Reyes-Lopez, F (eLife Sciences Publications Ltd, 2021)
The COVID-19 pandemic will likely take years to control globally, and constant epidemic surveillance will be required to limit the spread of SARS-CoV-2, especially considering the emergence of new variants that could hamper the effect of vaccination efforts. We developed a simple and robust-Phone Screen Testing (PoST)-method to detect positive SARS-CoV-2 individuals by RT-PCR testing of smartphone screen swab samples. We show that 81.3-100% of individuals with high-viral load SARS-CoV-2 nasopharyngeal positive samples also test positive for PoST, suggesting this method is effective in identifying COVID-19 contagious individuals. Furthermore, we successfully identified polymorphisms associated with SARS-CoV-2 Alpha, Beta and Gamma variants, in SARS-CoV-2 positive PoST samples. Overall, we report that PoST is a new non-invasive, cost-effective, and easy to implement smartphone-based smart alternative for SARS-CoV-2 testing, which could help to contain COVID-19 outbreaks and identification of variants of concern in the years to come. © 2021, eLife Sciences Publications Ltd. All rights reserved.